ANALISIS SHOOTING FINAL EUROBASKET 2017 ANTARA TIM BOLABASKET SLOVENIA DAN SERBIA - Derrydamawan, Briansyah Bhaskoro (Jurnal Kesehatan Olahraga, 2018)
This research aims to discover effectiveness of shooting on 2017 Eurobasket Final game between Slevenia and Serbia. The object of this research is Slovenia?s and Serbia?s basketball team. The subject of this research is shooting techniques based on player position Slovenia?s and Serbia?s basketball team. This research uses non-experimental research with descriptive analysis method and uses ex post facto data. Based on the result of this research, shooting percentage for Slovenia?s basketball team is 60% and shooting percentage for Serbia?s basketball team is 53%. And also obtained shooting percentage for each position from both team. From Slovenia?s team, best of them are point guard did 17 set shoots with 88% shooting percentage, shooting guard did six set shoots with 83% shooting percentage, small forward did some good shooting types, power forward did six set shoots with 83% shooting percentage  and center  did  not  shoot  a lot.  From  Serbia?s team, best of them are point guard did five lay ups with 75% shooting percentage, shooting guard did five lay ups with 100% shooting percentage, small forward did three set shoots with 100% shooting percentage, and center did six set shoots with 67% shooting percentage. The conclusion from this research is Slovenia?s basketball team win the game because they have a better shooting percentage (60%) than Serbia?s basketball team (53%). And, player on point guard position better do lay up shoot and set shoot. Player on shooting guard position better do lay up shoot and set shoot. Player on small forward position better do lay up shoot, set shoot, jump shoot, three points shoot, and slamdunk. Player on power forward position better do set shoot and jump shoot. Player on center position bettter do slamdunk.